ISSUES OF APPLYING GIS TECHNOLOGIES IN CREATING A MAP OF IRRIGATED LANDS - Madaminova Shokhidakhon Shavkatjon kizi (Western European Studies, 2025)
The use of geographic information systems (GIS) and remote sensing technologies in the process of identifying, classifying, and mapping irrigated lands is one of the most relevant scientific and practical areas today. In this study, for spatial and statistical assessment of the state of irrigated lands, analysis was carried out using modern GIS tools, including ArcGIS Pro, QGIS programs, as well as satellite images of Sentinel-2 MSI and Landsat 8 OLI. Using vegetation indices such as NDVI and NDWI, actively irrigated, weakly vegetated, and non-irrigated areas were identified. According to the research results, 57.3% of the analyzed area is actively irrigated, 23.8% of the area has weak vegetation, and 18.9% of the area is non-irrigated. The process was carried out on the basis of a technological methodology: data collection, analysis, spatial data processing, and creation of index maps. The methodological approach was developed on the basis of infographics and a graphical technological scheme. The research results showed that GIS technologies provide the ability to accurately, quickly, and visually assess the state of agricultural lands. This methodology can be effectively applied not only for scientific research, but also in practice - in resource management, optimization of irrigation systems, and environmental monitoring. In the future, this approach can be further improved by integrating with drone technologies, machine learning algorithms, and WebGIS platforms
Keywords: GIS technologies; irrigated lands; remote sensing